The Protective Effect of α‐Hederin, the Active Constituent of Nigella sativa, on Lung Inflammation and Blood Cytokines in Ovalbumin Sensitized Guinea Pigs. (21st August 2015) - Keyhanmanesh, Rana; Saadat, Saeideh; Mohammadi, Mostafa; Shahbazfar, Amir‐Ali; Fallahi, Maryam
Abstract : In the present study, the preventive effect of two different concentrations of α‐hederin, the active constituent of Nigella sativa, on lung inflammation and blood cytokines in ovalbumin sensitized guinea pigs was examined. Forty eight male adult guinea pigs were divided into control (C), sensitized (S) and sensitized pretreated groups; with thymoquinone (S+TQ), low dose (S+LAH) and high dose of α‐hederin (S+HAH) and inhaled fluticasone propionate (S+FP). The lung histopathology and blood levels of IL‐4, IFN‐γ and IL‐17 were assessed. Compared to sensitized animals, all pathological changes improved significantly in pretreated groups (p < 0.001 to p < 0.05). These improvements in α‐hederin pretreated groups were similar to S+TQ and S+FP groups except cellular infiltration in S+LAH and S+HAH groups which was lower than S+TQ group (p < 0.05). The blood IL‐4 and IL‐17 levels in S+HAH groups showed a significant decrease compared to S group (p < 0.05) which were similar to S+TQ and S+FP groups. The level of IFN‐γ in S+LAH and S+HAH groups increased significantly compared to S group (p < 0.05) which was higher than S+FP group (p < 0.05). Blood IL‐4 in S+HAH group was significantly lower than S+LAH group (p < 0.05). In conclusion, α‐hederin could attenuate the lung inflammation and improve the changes of cytokines like thymoquinone and fluticasone in used dosages. Copyright © 2015 John Wiley & Sons, Ltd.